LED BOOK LIGHT PANEL - G.KARTHIK REDDY, P.MAHESH BABU, K.RAVI KIRAN,D.NAVEEN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In the world of modern technology, product development concept is being flourished day by day in order to achieve customer satisfaction. Multi feature products have brought a tremendous change in modern age. These products are not only a magnificent sign of improvement of product development but also a reliable medium to ease customer’s day to day life. Today, customers are more likely to have a product of multi feature elements along with its aesthetic look. Considering customers aspiration as a focal point, this paper will develop a concept of multipurpose table lamp. The improved table lamp will provide a facility of certain number of products. This paper shows the construction of a multipurpose table lamp by gathering knowledge from customers and expert consultations. Various product development tools have been used to implement the desired concepts. Finally an economic analysis has been shown to justify the feasibility of the product in production